2014
DOI: 10.1016/j.cattod.2014.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Studies on water–gas-shift enhanced by adsorption and membrane permeation

Abstract: A new sorption enhanced membrane reactor (SEMR), consisting of a packed adsorbentcatalyst bed (10% CuO/CeO 2 catalyst and a hydrotalcite-derived Mg-Al mixed oxide) around a tubular Pd/Ag hollow fibre membrane, has been proposed to obtain high purity H 2 and simultaneous capture of CO 2 during the water gas shift reaction. The H 2 yield at 350ºC using the SER was 80%, which is 33% higher than that obtained in the traditional FBR and 18% higher than the corresponding thermodynamic equilibrium.However, due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…In this manner, H 2 is produced by mature and consolidated technologies from hydrocarbons at the first stages, integrating process intensification technologies and CO 2 sequestration, and it is progressively moved to renewable sources. At this point, the use of membrane technology is attracting the interest of the scientific community due to its potential for controlling CO 2 emissions and increasing energy efficiency [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In this manner, H 2 is produced by mature and consolidated technologies from hydrocarbons at the first stages, integrating process intensification technologies and CO 2 sequestration, and it is progressively moved to renewable sources. At this point, the use of membrane technology is attracting the interest of the scientific community due to its potential for controlling CO 2 emissions and increasing energy efficiency [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Relative to large-scale experimental demonstrations, simulations offer an inexpensive and less physically-intensive route towards the same goal. One example where simulation work could save time is validating a hypothesis mentioned by García-García et al 352 They suggested that uniform distribution of catalyst and sorbent along a fixed-bed reactor will not be the optimal configuration. Most of the gasification/reforming/WGS reactions occurs towards the feedstock inlet of the reactor, so it is more logical to have catalysts positioned near the reactor inlet and sorbents/membranes further down the reactor.…”
Section: Process Simulationmentioning
confidence: 70%
“…The large size of the fluidised reactor they used limited the shift effect from membrane permeation owing to a low membrane area-toreactor volume ratio. A compact design by combining catalyst and sorbents inside a membrane reactor which has a higher membrane area-to-reactor volume ratio was designed by García-García et al 352 They deployed a Cu-based catalyst and hydrotalcite sorbent in a palladium membrane reactor to enhance WGS, observing >90% CO conversion for the sorptionenhanced membrane reactor. This was an improvement relative to the 80% conversion obtained in the sorptionenhanced reactor and the 50% conversion for a traditional fixed-bed reactor.…”
Section: Comentioning
confidence: 99%
See 1 more Smart Citation
“…CO þ H 2 O % H 2 þ CO 2 D r H 0 298 ¼ À41 kJ/mol (2) its removal by the reaction CaO þ CO 2 % CaCO 3 D r H 0 298 ¼ À178 kJ/mol (3) results both in the higher conversion extent and better hydrogen purity.…”
Section: Introductionmentioning
confidence: 99%